Gender-Specific Association of Oxidative Stress and Inflammation with Cardiovascular Risk Factors in Arab Population. (31st March 2015) - Khadir, Abdelkrim; Tiss, Ali; Kavalakatt, Sina; Behbehani, Kazem; Dehbi, Mohammed; Elkum, Naser
Abstract : Background . The impact of gender difference on the association between metabolic stress and cardiovascular disease (CVD) remains unclear. We have investigated, for the first time, the gender effect on the oxidative and inflammatory stress responses and assessed their correlation with classical cardiometabolites in Arab population. Methods . A total of 378 adult Arab participants (193 females) were enrolled in this cross-sectional study. Plasma levels of CRP, IL-6, IL-8, TNF- α, ROS, TBARs, and PON1 were measured and correlated with anthropometric and cardiometabolite parameters of the study population. Results . Compared to females, males had significantly higher FBG, HbA1c, TG, and blood pressure but lower BMI, TC, and HDL ( P  < 0.05). After adjustment for BMI and WC, females had higher levels of ROS, TBARS, and CRP ( P  < 0.001) whereas males had increased levels of IL-8, IL-6, and TNF- α ( P  < 0.05). Moreover, after adjustment for age, BMI, and gender, the levels of TNF- α, IL-6, and ROS were associated with central obesity but not general obesity. Conclusion . Inflammation and oxidative stress contribution to CVD risk in Arab population linked to gender and this risk is better reflected by central obesity. Arab females might be at risk of CVD complications due to increased oxidative stress.